An exploration of whether the Policy on Financial Awards for Service Providers (Circular no. 17/2004) is a reasonable solution to the subject of welfare service financing - Lotvonen, Mari Tuulikki (Department of Social Development, 2024)
[pg28 is missing] Since 1975 the South African government has struggled to find a suitable way to finance welfare services that would meet both the welfare service providers' and the government's needs. In spite of several policy formulating attempts the solution has still to be found. The most recent policy document regarding welfare service financing is the Policy on Financial Awards to Service Providers (Circular No. 17/2004), which intends to transform the social service delivery system in South Africa. The research undertaken was empirical research, aiming to explore whether welfare organisations in the Western Cape can meet the transformation criteria as stipulated in the Policy on Financial Awards (RSA, 2004a) and obtain funding from sources other than the government. The research sample was selected using the purposive sampling method. Sample selection criteria was that an organisation must have received subsidies from the Provincial Administration Western Cape (PAWC) in the financial year 2003/2004, must employ four or more social workers and the head office must be located in an urban area within the greater Cape Town. Only twenty welfare organisations met the sampling criteria therefore the sample became the research population. All twenty organisations participated in the research, resulting in a one hundred percent (100%) response rate. The research design combined three quantitative and qualitative data collection methods - personal questionnaires developed by the researcher, informal interviews with respondents, and document analysis of audited financial statements for the year 2003/2004. The data was collected between May 2005 and August 2005. One transformation criterion is that welfare organisations' employment profiles must be reflective of the communities they provide services for. Based on the research findings, none of the welfare organisations meet this transformation criterion. If the Policy on Financial Awards is strictly applied, this lack of meeting the criterion is illegal in terms of South African labour legislation. In terms of service provision in rural areas the Policy definition was not precise, but the findings suggest that fifteen organisations (75% of the research population) are likely to face difficulties in meeting this transformation criterion. Based on the analysis of financial statements, seven organisations (35% of the research population) can be considered to be financially sustainable. In terms of obtaining funding from sources other than government the findings suggest that nine organisations (45% of the research population) have adequate fundraising strategies.